Efforts to Regenerate Islamic Youth through Religious Education - Candra, Bach Yunof; Agustian, Dhika Surya; Safitri, Balqis Angesti (Universitas Wiralodra, 2024)
The development of religious science in today's society is very undesirable and has become a taboo for the community itself, even though the community environment is Muslim. This interest impacts the next generations who will receive the Islamic leadership relay. It will not run smoothly, if the development of Islamic science in the community, especially in children and adolescents, is not considered by parents and community leaders there. The regeneration of Islamic youth is very necessary to hold the leadership relay that they will carry out in the future. However, how regeneration is formed must be considered every aspect so that religious understanding among children and adolescents can be widely spread and not become foreign to them. Both with a religious approach and activities based on religion itself can be used by the Islamic community as a medium for regeneration.